1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Symbolic logic

  1. Oct 5, 2007 #1
    the question is.
    1. (a>b). (b>c)
    2. c>-d
    3. b>e
    4. -d>f
    5. -e v -f

    We have to find -a v -c

    i can get so far then bam nothing! any help would be great thank you.

    6. a>b 1 simp
    7. b>-c 1,6, mp
    8. a>-c h.s.
  2. jcsd
  3. Oct 5, 2007 #2
    I'm confused by the first line. Is it A[tex]\rightarrow[/tex]B and B[tex]\rightarrow[/tex]C ?

    Anyways, you're close to a solution in 8. Do you know a relation between the implication and or operators? In other words, do you know a statement using implication that is logically equivalent to the statement -a v -c ?

    The problem is I don't follow your deduction of line 7, how do you get b>-c from a>b and b>c?

    If you can deduce -a v -c you're practically done.
    Last edited: Oct 5, 2007
  4. Oct 5, 2007 #3

    i deduced line seven (b>-c)
    taking line one which is ( a>b) and (b>-c)
    and line six (a>b).

    I dont know how to get the -a v-c.
  5. Oct 5, 2007 #4
    I see... In your original post you have b>c. Your deduction is correct.
  6. Oct 5, 2007 #5

    any idea what a next step would be? this one is driving me nuts
  7. Oct 5, 2007 #6
    I think you only need to find -A and you can make an Add to get -A v -C.
  8. Oct 5, 2007 #7
    I don't understand the (.) operator, What does mean?
  9. Oct 5, 2007 #8
    Hey you only need one step. If you reach to step 8 then you only need to make an implication of 8.

    P[tex]\rightarrow[/tex]Q:: -P v Q
  10. Oct 7, 2007 #9
    ok, i am still stuck i can not get -a then i can wedge in the last part.
  11. Oct 8, 2007 #10
    If you have a>-c by implication you have -a v -c
  12. Oct 9, 2007 #11


    User Avatar
    Gold Member

    some remarks, if you intended already to deduce from (a->b)&(b->c) by mp b->c why didn't you use simplification on it?
    anyway here's one proof:
    1. (a->b). (b->c)
    2. c->~d
    3. b->e
    4. ~d->f
    5. ~e v ~f
    6. a->b 1,simp
    7. a->e 3,6 hypothetical syllogism.
    8. f->~e 5,material conditional.
    9. ~d->~e 4,8, hypo syllogsim
    10. c->~e 2,9 h.s
    11. ~~e->~c 10, modus tollens.
    12. e->~c 11, double negation.
    13. ~e->~a 7,modus tollens.
    now you can take it yourself.

    p.s in questions in logic in the future take care on describing which rules of natural deduction you can use and which you cannot!
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Similar Threads for Symbolic logic
Logic Proposition Proof
Logic problem about tennis